A CRITICAL EXAMINATION OF VALUE-BASED APPROACHES IN EDUCATIONAL SYSTEMS - Muhammad Rahmanda; Muhammad Sultan Ale Tarigan; Justin Abrar; Muhammad Zhafran Syafiq Hasibuan; Abdul Afif Rahmansyah (PT. Radja Intercontinental Publishing, 2025)
This article examines the adverse effects of an education system that prioritizes academic grades above all else. Employing a qualitative approach, the study explores relevant literature and case studies to identify the implications of value orientation within educational contexts. The findings indicate that an excessive focus on grades may diminish students’ intrinsic motivation, foster academic dishonesty, and neglect the cultivation of character and social skills. The study recommends a reform toward a more holistic education system that emphasizes comprehensive individual development and personal growth.